Toward controlled geometric structure and surface property heterogeneities of TiO2 for lipase immobilization. (November 2021) - Zhou, Wenfeng; Zhou, Xiaohong; Zhuang, Wei; Lin, Rijia; Zhao, Ye; Ge, Lei; Li, Ming; Wu, Jinglan; Yang, Pengpeng; Zhang, Hongman; Zhu, Chenjie; Ying, Hanjie
Graphical abstract: Highlights: Surface property impacted more on immobilized lipase catalysis than geometric structure. Ethenyl triethoxy silane (ETS) modified titanium oxide (TiO2 ) exhibited the best performance. The catalytic activity of lipase immobilized on functionalized TiO2 reached up to 428.04 %. The activity of immobilized lipase retains almost 95 % after stored at 4 °C for 8 weeks. Abstract: To effectively immobilize an enzyme while maintaining its high activity and stability, the design of supports with controlled geometric structures and heterogeneous surface properties is desirable. Towards this goal, heterogeneous titanium dioxide (TiO2 ) surfaces with controlled pore sizes were synthesized in this study and used to efficiently immobilize lipase. The immobilized lipase activity increased by a factor of 1.31 with an increase in the TiO2 pore size from 11.46 to 21.14 nm. The highest protein loading of 15.52 mg/g was achieved in ethenyl triethoxy silane (ETS)-modified TiO2 (E-P25) after immobilizing the enzymes at 30 ℃, pH 7.33 for 3 h and using a protein concentration in solution of 0.176 mg/mL. Among the different surface functionalities, the highest activity yield of 428.04 % was accomplished by using TiO2 calcinated at 650 ℃ and modified by ETS as immobilization support. The immobilized enzymes showed excellent storage stability and retained almost 95 % of their activity after being stored at 4 ℃ for 8 weeks. This research provides experimental evidence that highlights the importance of studying of enzyme immobilization on the supports with synergistically designed geometric structures and surface chemical properties.